SISTEM INFORMASI EVALUASI DOSEN PADA PROGRAM STUDI KOMPUTER DAN SISTEM INFORMASI UGM MENGGUNAKAN FITUR SINGLE SIGN ON - , KHOIRUL UMAM M, Faizah, S.Kom., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lecturer is one of the most important elements in a system of education at the college. To produce high quality of graduates, it needs quality improvement in education. Improved performance of lecturer is one way to improve education quality. In the learning process, the evaluation process is necessity to measure the extent of which level of the lecturer's performance in teaching. Development of information systems faculty evaluation has the function to determine the performance of lecturers in courses Computer and Information Systems. This information system is built using the programming language PHP, CodeIgniter framework, MySQL database, and Twitter Bootstrap in interface, as well as adding a single sign on feature for students to access the system. This information system provides services such as aspects of assessment management, management assessment, the assessment results are displayed graphically, report printing, and also process of filling the questionnaire by the students. This information system give positive communication between students and lecturer in order to improve the quality of learning.